Nesprin‐1 and nesprin‐2 regulate endothelial cell shape and migration. Issue 7 (25th June 2014) - King, Samantha J.; Nowak, Karolin; Suryavanshi, Narendra; Holt, Ian; Shanahan, Catherine M.; Ridley, Anne J.
<x xml:space="preserve">Abstract</x> Nesprins are large multi‐domain proteins that link the nuclear envelope to the cytoskeleton and nucleoskeleton. Here we show that nesprin‐1 and nesprin‐2 play important roles in regulating cell shape and migration in endothelial cells. Nesprin‐1 or nesprin‐2 depletion by RNAi increased endothelial cell spread area and the length of cellular protrusions, as well as stimulating stress fibre assembly which correlated with an increase in F‐actin levels. Nuclear area was also increased by nesprin depletion, and localization of the inner nuclear membrane protein emerin to the nuclear envelope was reduced. Depletion of nesprin‐1 or nesprin‐2 reduced migration of endothelial cells into a cell‐free area, and decreased loop formation in an in vitro angiogenesis assay. Taken together, our results indicate that nesprin‐1 and nesprin‐2 both regulate nuclear and cytoplasmic architecture, which we propose leads to their effects on endothelial cell migration and angiogenic loop formation. © 2014 The Authors Cytoskeleton Published by Wiley Periodicals, Inc.